SISTEM INFORMASI PENGELOLAAN KOPERASI BERBASIS WEBSITE - Ismail, Abdul Rahman; Sidik, Zainudin (Smart Education, 2025)
Abstract: This research aims to design and develop a web-based cooperative management information system that can simplify administrative processes, particularly in loan applications and installment payments. The system is built using the Agile method, which allows development to be carried out in stages and adapts flexibly to user needs. The main features developed include loan data management, payment recording, member data management, and the automatic presentation of financial reports. This system is designed to improve the efficiency of cooperative management and provide quick and transparent access to information for members. Testing is carried out using white-box and black-box methods to ensure that the system functions properly both in terms of internal logic and external appearance and functionality. The results of the testing show that all features work as expected and support the overall operations of the cooperative. This system is expected to be a practical and effective digital solution for cooperative management. Furthermore, this system can be further developed in line with the future growth needs of the cooperative. Keywords: Information System; Cooperative; Website. Abstrak: Penelitian ini bertujuan untuk merancang dan mengembangkan sistem informasi pengelolaan koperasi berbasis website yang dapat mempermudah proses administrasi, khususnya dalam pengajuan pinjaman dan pembayaran angsuran. Sistem ini dibangun dengan metode Agile, yang memungkinkan pengembangan dilakukan secara bertahap dan menyesuaikan kebutuhan pengguna secara fleksibel. Fitur utama yang dikembangkan meliputi pengelolaan data pinjaman, pencatatan pembayaran, manajemen data anggota, serta penyajian laporan keuangan secara otomatis. Sistem ini dirancang untuk meningkatkan efisiensi kerja pengurus koperasi dan memberikan kemudahan akses informasi kepada anggota secara cepat dan transparan. Pengujian dilakukan menggunakan metode whitebox dan blackbox untuk memastikan bahwa sistem berfungsi dengan baik dari sisi logika internal maupun tampilan dan fungsionalitas eksternal. Hasil pengujian menunjukkan bahwa seluruh fitur berjalan sesuai harapan dan mendukung proses kerja koperasi secara menyeluruh. Sistem ini diharapkan mampu menjadi solusi digital yang praktis dan efektif dalam pengelolaan koperasi. Selain itu, sistem ini dapat dikembangkan lebih lanjut sesuai dengan pertumbuhan kebutuhan koperasi di masa mendatang. Kata kunci: Sistem Informasi; Koperasi; Website.